Prompt gamma spectroscopy for absolute range verification of 12C ions at synchrotron-based facilities - Dal Bello, Riccardo; Brons, Stephan; Seco, Joao (Physics in medicine and biology, 2020)
The physical range uncertainty limits the exploitation of the full potential of charged particle therapy. In this work, we face this issue aiming to measure the absolute Bragg peak position in the target. We investigate p, 4He, 12C and 16O beams accelerated at the Heidelberg Ion-Beam Therapy Center. The residual range of the primary 12C ions is correlated to the energy spectrum of the prompt gamma radiation. The prompt gamma spectroscopy method was demonstrated for proton beams accelerated by cyclotrons and is developed here for the first time for heavier ions accelerated by a synchrotron. We develop a detector system that includes (i) a spectroscopic unit based on cerium(III) bromide and bismuth germanium oxide scintillating crystals, (ii) a beam trigger based on an array of scintillating fibers and (iii) a data acquisition system based on a FlashADC. We test the system in two different scenarios. In the first series of experiments, we detect and identify 19 independent spectral lines over a wide gamma energy spectrum in the presence of the four ion species for different targets, including a water target with a titanium insert. In the second series of experiments, we introduce a collimator aiming to relate the spectral information to the range of the primary particles. We perform extensive measurements for a 12C beam and demonstrate submillimetric precision for the measurement of its Bragg peak position in the experimental setup. The features of the energy and time spectra for gamma radiation induced by p, 4He and 16O are investigated upstream and downstream from the Bragg peak position. We conclude the analysis by extrapolating the required future developments, which would be needed to achieve range verification with a 2 mm accuracy during a single fraction delivery of physical dose.
Die Zahl "12" ist im Haupttitel hochgestellt
Gesehen am 09.09.2020